Clinical picture of S-adenosylhomocysteine hydrolase deficiency resembles phosphomannomutase 2 deficiency - Honzík, Tomáš; Magner, Martin; Krijt, Jakub; Sokolová, Jitka; Vugrek, Oliver; Belužić, Robert; Barić, Ivo; Hansíková, Hana; Elleder, Milan; Veselá, Kateřina; Bauerová, Lenka; Ondrušková, Nina; et al. (Molecular genetics and metabolism, 2012)
We report on the seventh known patient with S-adenosylhomocysteine hydrolase (SAHH) deficiency presenting at birth with features resembling phosphomannomutase 2 (PMM2-CDG Ia) deficiency. Plasma methionine and total homocysteine levels were normal at 2 months and increased only after the 8th month of age. SAHH deficiency was confirmed at 4.5 years of age by showing decreased SAHH activity (11% in both erythrocytes and fibroblasts), and compound heterozygosity for a known mutation c.145C>T (p.R49C) and a novel variant c.211G>A (p.G71S) in the AHCY gene. Retrospective analysis of clinical features revealed striking similarities between SAHH deficiency and the PMM2-CDG Ia.
Keywords: mutace; heterozygot; diferenciální diagnóza; Female; novorozenec; Adenosylhomocysteinase; ženské pohlaví; adenosylhomocysteinasa; Fibroblasts; erytrocyty; Congenital Disorders of Glycosylation; Methionine; lidé; Heterozygote; Infant, Newborn; vrozené poruchy glykosylace; Mutation; fibroblasty; Diagnosis, Differential; homocystein; Erythrocytes; Phosphotransferases (Phosphomutases); methionin; Homocysteine; fosfotransferasy (fosfomutasy); Humans